Method for producing polymer solid electrolyte

A novel production method for solid polymer electrolytes using cross-linkable functional groups and a freezing/thawing process reduces crystallinity, enhancing ionic conductivity and enabling continuous production, addressing the limitations of conventional high-temperature drying methods.

JP2025502087AActive Publication Date: 2025-01-24LG ENERGY SOLUTION LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024540985
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-05-31
Filing Date
2023-05-31
Publication Date
2025-01-24
Estimated Expiration
2043-05-31

AI Technical Summary

Technical Problem

Conventional polymer solid electrolytes manufactured through high-temperature drying processes suffer from high crystallinity, which limits ionic conductivity and chain mobility, making them brittle and difficult to produce in a continuous process without the use of plasticizers.

Method used

A method involving the formation of a polymer solution with cross-linkable functional groups, application onto a base film, freezing, thawing, and repeating the process to create a crosslinked structure, reducing crystallinity and enabling a continuous roll-to-roll production of a solid polymer electrolyte.

Benefits of technology

The method improves ionic conductivity and allows for mass production of a solid polymer electrolyte with reduced brittleness, achieving properties comparable to liquid electrolytes while maintaining stability and elasticity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025502087000001_ABST
    Figure 2025502087000001_ABST
Patent Text Reader

Abstract

The present invention relates to a method for producing a polymer solid electrolyte, and the polymer solid electrolyte produced by freezing and thawing includes a cross-linked structure formed by a cross-linking functional group, and the cross-linked structure includes (a) a cross-link between the cross-linking functional groups, (b) a cross-link between the cross-linking functional group and a solvent, and (c) a bond between the cross-linking functional group and a lithium salt, so that the crystallinity of the polymer solid electrolyte can be reduced and the ionic conductivity can be improved without using a separate plasticizer. In addition, the method can be carried out in a continuous process and in a large volume.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0066932 filed May 31, 2022 and Korean Patent Application No. 10-2023-0070122 filed May 31, 2023, and incorporates all contents disclosed in the documents of said Korean patent applications as part of this specification.

[0002] The present invention relates to a method for producing a polymer solid electrolyte. [Background technology]

[0003] Lithium-ion batteries that use liquid electrolytes have a structure in which the negative and positive electrodes are separated by a separator, so if the separator is damaged due to deformation or external impact, a short circuit can occur, which can lead to risks such as overheating and explosion. Therefore, the development of a solid electrolyte that can ensure safety in the field of lithium-ion secondary batteries is a very important issue.

[0004] Lithium secondary batteries using solid electrolytes have the advantage of increasing the safety of the battery, preventing electrolyte leakage, improving battery reliability, and making it easier to manufacture thin batteries. In addition, because lithium metal can be used for the negative electrode, the energy density can be improved, and this makes it possible to apply them to small secondary batteries as well as large-capacity secondary batteries for electric vehicles, and they are attracting attention as next-generation batteries.

[0005] Among solid electrolytes, polymer solid electrolytes may use either ion-conductive polymer materials or inorganic materials such as oxides and sulfides that have ion-conductive properties, but hybrid materials that combine polymer materials and inorganic materials have also been proposed.

[0006] Such conventional polymer solid electrolytes were manufactured through solution casting and high-temperature drying processes. However, conventional polymer solid electrolyte manufacturing technology had a limitation in that it was difficult to manufacture polymer solid electrolytes with improved ionic conductivity due to the high crystallinity of crystalline polymers or semi-crystalline polymers. In other words, the high crystallinity of polymers inhibits the mobility of polymer chains, restricting the movement of lithium ions inside the polymer solid electrolyte, making it difficult to improve the ionic conductivity of the polymer solid electrolyte.

[0007] For example, a conventional polymer solid electrolyte can be manufactured by forming a coating film using polyvinyl alcohol (PVA) containing a hydroxyl group, which is a cross-linking functional group, as a polymer, and then performing a high-temperature drying process. Specifically, the PVA is dissolved in water to prepare a PVA aqueous solution, and the PVA aqueous solution is applied to a substrate by solution casting to form a coating film, and the coating film is dried at room temperature or a high temperature to manufacture a PVA film-shaped polymer solid electrolyte. In this case, high temperature means 80°C or higher, which is the glass transition temperature (Tg) of PVA. In the drying process, after the water evaporates, hydrogen bonds are formed between the cross-linking functional groups contained in the PVA, and the hydrogen bonds cause polymer chain folding, resulting in a phenomenon in which the crystallinity of the polymer film is increased. The higher the crystallinity, the more brittle the polymer film is formed. In a polymer film with high crystallinity and brittleness, the chain mobility of the polymer chain is reduced, and when dissociated ions exist inside the polymer film, the ion mobility is also significantly reduced. For this reason, a typical PVA film produced by forming a coating film and then drying it at a high temperature as described above exhibits physical properties that are not suitable as a polymer solid electrolyte for lithium secondary batteries.

[0008] In order to overcome these limitations of polymer solid electrolytes, a technology was developed to improve the mobility of polymer chains by adding a plasticizer to a crystalline or semi-crystalline polymer, thereby improving the ionic conductivity of the polymer solid electrolyte. However, when using a plasticizer, it is sometimes difficult to set process conditions because appropriate dispersion and miscibility between the polymer and the plasticizer must be ensured. In addition, when a liquid plasticizer is used, the compatibility with the polymer decreases, making it difficult to carry out the manufacturing process with the polymer solid electrolyte.

[0009] Therefore, there is a need for technological development of a method for producing a polymer solid electrolyte in the form of a free-standing film that can be continuously processed without using a separate additive such as a plasticizer. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] China Patent Application Publication No. 112259788 Summary of the Invention [Problem to be solved by the invention]

[0011] An object of the present invention is to provide a method for producing a polymer solid electrolyte which allows for improved ion conductivity and a continuous process.

[0012] Another object of the present invention is to provide an all-solid-state battery including a polymer solid electrolyte produced by the above-mentioned production method. [Means for solving the problem]

[0013] Technical Solutions In order to achieve the above objectives, The present invention relates to (1) preparing a polymer solution containing a cross-linking functional group and a solution for forming a polymer solid electrolyte containing a lithium salt; (2) unwinding the base film using an unwinder and feeding the base film to a conveying path; (3) applying the polymer solid electrolyte forming solution onto the substrate film to form a coating film; (4) conveying the substrate film having the coating film formed thereon to a freezing section and freezing the coating film; (5) transferring the substrate film on which the frozen coating film is formed to a thawing section, and thawing the frozen coating film to manufacture a polymer solid electrolyte layer; and (6) The present invention provides a method for producing a polymer solid electrolyte, the method including a step of winding and recovering the substrate film including the polymer solid electrolyte layer using a rewinder.

[0014] The present invention also provides an all-solid-state battery comprising a polymer solid electrolyte produced by the production method of the present invention. Effect of the Invention

[0015] The method for preparing a polymer solid electrolyte according to the present invention can reduce the crystallinity of the polymer by using a cross-linked structure formed by cross-linking functional groups contained in the polymer and a structure including amorphous polymer chains, thereby improving ionic conductivity, and can reduce brittleness, ductility, and viscosity due to the structural features.

[0016] Furthermore, the method for producing a polymer solid electrolyte according to the present invention can produce a polymer solid electrolyte in a continuous process, making mass production possible. [Brief description of the drawings]

[0017] [Figure 1] 1 is a flowchart of a method for producing a polymer solid electrolyte of the present invention. [Diagram 2] 1 is a graph showing the tendency of the ionic conductivity of the electrolyte depending on the molar ratio ([Li] / [OH]) of the cross-linking functional group and the lithium salt. [Diagram 3]Photographs showing the morphology of electrolytes depending on the molar ratio of cross-linking functional groups to lithium ([Li] / [OH]). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] In the following, the present invention will be described in further detail to aid in understanding the invention.

[0019] The terms and words used in this specification and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a manner that is consistent with the technical idea of ​​the present invention, based on the principle that an inventor can appropriately define the concept of a term in order to best describe his or her invention.

[0020] The term "crosslinked structure" used herein refers to a structure including a three-dimensional frame formed by polymer chains and an internal space of the frame. The polymer chains are formed by crosslinking involving crosslinking functional groups contained in the polymer. The crosslinked structure has a three-dimensional shape and is in a form in which the polymer chains are intertwined with each other, so it can also be called a three-dimensional network structure.

[0021] Method for producing polymer solid electrolyte The present invention relates to a method for producing a polymer solid electrolyte, and the method for producing a polymer solid electrolyte of the present invention includes the steps of: (1) preparing a polymer solution containing a cross-linking functional group and a solution for forming a polymer solid electrolyte containing a lithium salt; (2) unwinding the base film using an unwinder and feeding the base film to a conveying path; (3) applying the polymer solid electrolyte forming solution onto the substrate film to form a coating film; (4) conveying the substrate film having the coating film formed thereon to a freezing section and freezing the coating film; (5) transferring the substrate film having the frozen coating film formed thereon to a thawing section and thawing the frozen coating film to manufacture a polymer solid electrolyte layer; and (6) The method includes a step of winding and recovering the substrate film including the polymer solid electrolyte layer using a rewinder.

[0022] The step (1) is a step of preparing an aqueous polymer solution containing a cross-linkable functional group and a solution for forming a polymer solid electrolyte containing a lithium salt.

[0023] In the present invention, the polymer containing a crosslinkable functional group is a polymer containing a crosslinkable functional group that can form a crosslinked structure by (a) crosslinking between the crosslinkable functional groups, (b) crosslinking between the crosslinkable functional group and a solvent, and (c) bonding between the crosslinkable functional group and a lithium salt. The bonds (a), (b), and (c) will be described in more detail below.

[0024] For example, the cross-linkable functional group may include one or more selected from the group consisting of a hydroxyl group, a carboxyl group, and an amide group.

[0025] In addition, the weight average molecular weight (Mw) of the polymer containing the crosslinkable functional group is 80,000 g / mol to 130,000 g / mol, specifically, 80,000 g / mol or more, 83,000 g / mol or more, or 85,000 g / mol or more, and 90,000 g / mol or less, 110,000 g / mol or less, or 130,000 g / mol or less. If the weight average molecular weight (Mw) of the polymer containing the crosslinkable functional group is less than 80,000 g / mol, the bond by the crosslinkable functional group may not be formed sufficiently to obtain a crosslinked structure. If the weight average molecular weight (Mw) of the polymer containing the crosslinkable functional group exceeds 130,000 g / mol, the entanglement of the polymer chain increases in the polymer aqueous solution, and the solvent penetration rate into the inside of the polymer chain decreases. This may accelerate gelation of the polymer, reduce the solubility of the polymer, and inhibit smooth bonding via cross-linking functional groups, making it difficult to form a cross-linked structure.

[0026] In addition, the polymer containing the cross-linking functional group has a feature that phase separation between the polymer and the solvent is smoothly performed in the polymer solution, and the bonds (a), (b), and (c) are well formed by the cross-linking functional group contained in the phase-separated polymer in the step of freezing the coating film in the step (4).

[0027] Examples of the polymer containing the cross-linkable functional group include polyvinyl alcohol (PVA), gelatin, methylcellulose, agar, dextran, poly(vinyl pyrrolidone), polyethylene oxide, poly(acrylic amide), poly(acrylic acid), PAA, starch-carboxymethyl cellulose, hyaluronic acid-methylcellulose, chitosan, poly(N-isopropylacrylamide), and amino-terminated polyethylene glycol. Preferably, the polymer having a cross-linkable functional group is polyvinyl alcohol, which is advantageous in that phase separation between the polyvinyl alcohol and the solvent is efficiently performed in the step of freezing the coating film in the step (4), and the polyvinyl alcohol forms a cross-linked structure through the bonds (a), (b), and (c) derived from the cross-linkable functional group of the polyvinyl alcohol phase-separated from the solvent.

[0028] In the present invention, the lithium salt is contained in a dissociated state in the internal space of the cross-linked structure, and can improve the ionic conductivity of the polymer solid electrolyte.

[0029] Furthermore, the lithium salt forms a bond with the (c) cross-linking functional group described below, thereby preventing the generation of crystallinity in the polymer solid electrolyte and, at the same time, promoting the formation of amorphous polymer chains.

[0030] The lithium salts include LiNO3, LiOH, LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10 , LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, CF3SO3Li, LiSCN, LiC(CF3SO2)3, (CF3SO2)2NLi, and (FSO2)2NLi.

[0031] In the present invention, the molar ratio ([Li] / [G]) of the crosslinkable functional group ([G]) of the polymer containing the crosslinkable functional group and the lithium ([Li]) of the lithium salt contained in the polymer solid electrolyte is 0.1 or more and less than 0.5, specifically, more than 0.1, 0.2 or more, or 0.3 or more, and 0.4 or less or less than 0.5. If the molar ratio ([Li] / [G]) is 0.1 or less, the content of the lithium salt may decrease, and the ionic conductivity of the polymer solid electrolyte may decrease. If the molar ratio ([Li] / [G]) is 0.5 or more, the content of the polymer containing the crosslinkable functional group may decrease, and the bonds (a), (b), and (c) may not be sufficiently formed, which may increase the crystallinity and decrease the ionic conductivity. If the crosslinkable functional group is a hydroxyl group (OH - ), the [G] can be expressed as [OH] or [O].

[0032] The solvent used in preparing the polymer solution is a polar solvent, and may be, for example, water, that is, the polymer solution may be an aqueous polymer solution.

[0033] The concentration of the polymer solution containing a crosslinkable functional group can be appropriately adjusted in consideration of the degree to which the coating process can proceed smoothly when the polymer solid electrolyte forming solution is applied to the substrate film. For example, the polymer containing a crosslinkable functional group may be contained in an amount of 5 wt% to 20 wt%, specifically, 5 wt% or more, 7 wt% or more, or 9 wt% or more, and 13 wt% or less, 17 wt% or less, or 20 wt% or less, based on the total weight of the polymer solution containing a crosslinkable functional group. If the polymer containing a crosslinkable functional group is contained in an amount of less than 5 wt%, the concentration may be excessively diluted and may run off when applied to the substrate film, and if it is contained in an amount of more than 20 wt%, it may be difficult to dissolve the lithium salt at a desired concentration in the polymer solution, making it difficult to apply it in a uniform thin film.

[0034] The step (2) is a step of unwinding the base film using an unwinder and supplying it to a transport path.

[0035] The unwinder unwinds and supplies the base film wound in a roll to a predetermined transport path, and can unwind and supply the base film by its own drive, and can finally unwind and supply the base film by the drive force of a rewinder that winds up the base film including the polymer solid electrolyte layer.

[0036] Therefore, the method for producing the polymer solid electrolyte of the present invention is a roll-to-roll process.

[0037] The substrate film is not particularly limited as long as it can function as a support on which the polymer solid electrolyte forming solution is applied, for example, the substrate film is stainless steel (SS, Stainless Steel), polyethylene terephthalate film, polytetrafluoroethylene film, polyethylene film, polypropylene film, polybutene film, polybutadiene film, vinyl chloride copolymer film, polyurethane film, ethylene-vinyl acetate copolymer film, ethylene-propylene copolymer film, ethylene-ethyl acrylate copolymer film, ethylene-methyl acrylate copolymer film, or polyimide film.

[0038] The step (3) is a step of coating the polymer solid electrolyte forming solution on the substrate film to form a coating film.

[0039] The coating method in the present invention is not particularly limited as long as it can coat the polymer solid electrolyte solution on the substrate film in the form of a film, for example, bar coating, roll coating, spin coating, slit coating, die coating, blade coating, comma coating, slot die coating, lip coating, spray coating, or solution casting.

[0040] As an embodiment of the present invention, a solution casting method may be used. More specifically, the polymer solid electrolyte forming solution prepared in step (1) may be placed in a mixer, and the mixer may be positioned above a substrate film, and the polymer solid electrolyte forming solution may be continuously cast onto the substrate film fed through a transport path to form a coating film.

[0041] The step (4) is a step of conveying the substrate film on which the coating film is formed to a freezing section to freeze the coating film, and a polymer solid electrolyte can be manufactured in the step (4). The polymer solid electrolyte of the present invention includes an amorphous polymer chain having a cross-linked structure and the cross-linkable functional group, and the amorphous polymer chain having the cross-linked structure and the cross-linkable functional group is formed by freezing the coating film. The polymer solid electrolyte of the present invention includes the amorphous polymer chain and a lithium salt in an internal space formed in the cross-linked structure, and the lithium salt is included in a dissociated state.

[0042] The cross-linked structure is formed by forming localized crystallites of some of the cross-linking functional groups contained in the polymer, and the localized crystallites act as cross-linkable junction points to cross-link. Here, the microcrystals refer to a shape resembling a knot formed by entangling threads, unlike a crystal structure formed by folding of polymer chains.

[0043] The cross-linked structure includes (a) a cross-link between cross-linkable functional groups, (b) a cross-link between the cross-linkable functional group and a solvent, and (c) a bond between the cross-linkable functional group and a lithium salt, and the cross-linked structure is formed by inducing the bonds of (a), (b), and (c) by the cross-linkable functional group.

[0044] In the present invention, the (a) cross-linking bond between the cross-linking functional groups includes a hydrogen bond between the cross-linking functional groups. For example, the hydrogen bond is an OH - The hydrogen bonds between the

[0045] If the cross-linked structure is composed only of cross-links between the (a) cross-linkable functional groups, crystallinity may occur in the polymer solid electrolyte, resulting in a decrease in ionic conductivity.

[0046] However, since the cross-linked structure includes not only the (a) cross-linking between the cross-linking functional groups but also the (b) cross-linking between the cross-linking functional group and the solvent and the (c) bond between the cross-linking functional group and the lithium salt, the occurrence of crystallinity in the polymer solid electrolyte can be prevented.

[0047] In the present invention, the cross-linking bond between the (b) cross-linkable functional group and the solvent may include a hydrogen bond. For example, the hydrogen bond may be an OH - and H + In this case, H + may be derived from an aqueous solvent.

[0048] The (b) cross-linking between the cross-linkable functional group and the solvent means hydrogen bonding between the cross-linkable functional group and a portion of the solvent remaining after freezing and the thawing process in step (5) described below.

[0049] In addition, the crosslinking between the (b) crosslinkable functional group and the solvent interferes with the crosslinking between the (a) crosslinkable functional groups, and the crosslinked structure is not composed only of the crosslinking between the (a) crosslinkable functional groups, so that an increase in the crystallinity of the polymer solid electrolyte can be prevented. The solvent may contain water.

[0050] In the present invention, the bond between the (c) crosslinkable functional group and the lithium salt may include a bond due to Lewis acid-base interaction, for example, the bond may be an OH - and Li + is a combination of:

[0051] The bond between the (c) cross-linkable functional group and the lithium salt interferes with the cross-linking between the (a) cross-linkable functional groups and the (b) cross-linking between the cross-linkable functional group and the solvent, and the cross-linked structure is not composed only of the cross-linking between the (a) cross-linkable functional groups, so that the generation of crystallinity in the polymer solid electrolyte can be prevented and at the same time, the formation of amorphous polymer chains can be promoted. As the amorphous polymer chains are formed, the mobility of the polymer chains is improved, and therefore the hopping effect of the lithium ions is increased, and the ionic conductivity of the polymer solid electrolyte can be improved.

[0052] In the present invention, the amorphous polymer refers to a polymer chain formed by cross-linking functional groups, which does not form crystals due to regular folding of the polymer chain and exists in a free state of behavior, i.e., the amorphous polymer chain includes a polymer containing cross-linking functional groups that do not form bonds such as (a), (b) and (c).

[0053] Due to the cross-linked structure, the polymer solid electrolyte is not easily cut or destroyed, and can function as an electrolyte support that stably contains lithium ions.

[0054] In addition, the amorphous polymer chains allow the polymer solid electrolyte to exhibit elasticity and minimize brittleness, which is a property that the electrolyte is easily broken. The polymer chains have excellent polymer chain mobility, which improves the mobility of lithium ions within the electrolyte, thereby providing a polymer solid electrolyte with improved ion conductivity.

[0055] In addition, in step (4), phase separation may occur between the polymer and water contained in the aqueous polymer solution containing cross-linking functional groups used to form the coating film. The phase separation occurs because the strength of the hydrogen bonds between the water molecules is stronger than that between the cross-linking functional groups and the water molecules. The water molecules aggregated by the hydrogen bonds between the water molecules exist as an ice phase due to the freezing in step (4). As a result, the number of cross-linking functional groups that form hydrogen bonds through their interaction with the water molecules is significantly reduced.

[0056] That is, in the step of freezing the coating film, the polymer and water contained in the polymer aqueous solution must first undergo phase separation, and the phase separation is induced by hydrogen bonds between water molecules. As a result, the main target of the freezing step is the water molecules that induce phase separation. Alternatively, the targets of the freezing step after phase separation has been induced to a certain extent are the water molecules and the polymer.

[0057] Due to the phase separation, the inside of the coating film is divided into (i) a polymer-poor phase and (ii) a polymer-rich phase.

[0058] The (i) polymer-poor phase is a portion that contains water molecules that are aggregated by hydrogen bonds between water molecules, and exists in an ice phase, which can also be called a free water state.

[0059] The (ii) polymer-rich phase is a portion containing polymers that have been phase-separated from water. The phase-separated polymers are polymers containing cross-linking functional groups that have been freed from interactions with water molecules, and after phase separation, they are in a free state and do not form crystals through regular folding, but exist in an amorphous state with relatively free behavior, which is called an amorphous polymer chain.

[0060] In addition, some of the cross-linkable functional groups contained in the phase-separated polymer act as cross-linkable junction points where localized microcrystals can cross-link, forming a cross-linked structure including the bonds (a), (b), and (c).

[0061] The freezing of the coating film in the step (4) can be carried out by appropriately selecting conditions that can freeze the coating film. For example, the freezing temperature can be -30°C to -10°C, and more specifically, the freezing temperature is -30°C or higher, -25°C or higher, or -23°C or higher, and -18°C or lower, -15°C or lower, or -10°C or lower. If the freezing temperature is lower than -30°C, cracks may occur in the coating film, and if it is higher than -10°C, phase separation between the polymer and water may not be sufficiently performed, making it difficult to form an amorphous polymer chain region. The freezing can be carried out in consideration of a sufficient freezing time within a range of 20 to 30 hours.

[0062] The freezing section is located in a section where a coating film is formed on a base film and the base film on which the coating film is formed is transported to a rewinder, and is configured with a plurality of units.

[0063] In the past, polymer solid electrolytes were manufactured through a high-temperature drying process, but in this case, the mobility of polymer chains was hindered due to the high crystallinity of the crystalline or semi-crystalline polymer, which restricted the movement of lithium ions inside the polymer solid electrolyte, resulting in low ionic conductivity.

[0064] Therefore, in the present invention, a plasticizer is not used instead of a high-temperature drying process, and a freezing process is performed to induce (a) cross-linking between cross-linking functional groups, (b) cross-linking between the cross-linking functional groups and a solvent, and (c) bonding between the cross-linking functional groups and a lithium salt, by the cross-linking functional groups contained in the polymer, thereby preventing crystallization of the polymer. As a result, a polymer solid electrolyte with improved ionic conductivity can be produced.

[0065] The step (5) is a step of conveying the substrate film having the frozen coating film formed thereon to a thawing section to thaw the frozen coating film, thereby manufacturing a polymer solid electrolyte layer.

[0066] In the step (5), the ice contained in the polymer-poor phase (i) melts and evaporates, thereby producing a polymer solid electrolyte having an increased free volume.

[0067] The thawing can be performed by appropriately selecting conditions that allow the frozen coating film to be thawed to a degree that allows it to be applied to a polymer solid electrolyte. For example, the thawing temperature is 15° C. to 35° C., or room temperature (25° C.). If the thawing temperature is less than 15° C., the efficiency of drying water after thawing (ice melting) may decrease, and if it exceeds 35° C., the coating film may shrink and wrinkle or warp may occur.

[0068] As described above, the bonds of (a), (b) and (c) are induced by the step (4) of freezing the coating film and the step (5) of thawing the frozen coating film, forming a cross-linked structure and an amorphous polymer chain.

[0069] Therefore, steps (4) and (5) can be repeatedly performed, and the degree of formation of the cross-linked structure can be adjusted depending on the number of times the steps (4) and (5) are repeated. When steps (4) and (5) are regarded as one cycle, step (4) of freezing the coating film and step (5) of thawing the frozen coating film can be performed for one or more cycles, two or more cycles, three or more cycles, or five or more cycles. The upper limit of the cycles is not particularly limited, and may be 10 cycles or less, 13 cycles or less, or 15 cycles or less. As the cycles increase within the above range, more cross-linked structures are formed, and thus the modulus and strength of the polymer solid electrolyte are increased.

[0070] When the thawing is completed in the step (5), the coating film can be used as a polymer solid electrolyte.

[0071] The thawing section is located within a section where the base film on which the frozen coating film is formed is transported to a rewinder, and is composed of a plurality of stages.

[0072] After step (5) and before step (6), the method may further include a step of immersing the polymer solid electrolyte layer in a liquid electrolyte and then drying it.

[0073] By further including this step, the ionic conductivity of the polymer solid electrolyte can be further improved by the liquid electrolyte, which is also contained in the inner space of the cross-linked structure.

[0074] The liquid electrolyte may be any liquid electrolyte commonly used in the art, and the composition of the liquid electrolyte is not particularly limited as long as it can be used in a lithium secondary battery. For example, the liquid electrolyte may include a lithium salt and a non-aqueous solvent. The lithium salt is any one of the lithium salts described above. The non-aqueous solvent may include one or more selected from the group consisting of propylene carbonate (PC), ethylene carbonate (EC), vinylene carbonate (VC), diethyl carbonate (DEC), dimethyl carbonate (DMC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), tetrahydrofuran (THF), 2-methyltetrahydrofuran (2MeTHF), dioxolane (DOX), dimethoxyethane (DME), diethoxyethane (DEE), γ-butyrolactone (GBL), acetonitrile (AN), and sulfolane.

[0075] The liquid electrolyte is contained in an amount of 1 to 5% by weight based on the total weight of the polymer solid electrolyte. If the content of the liquid electrolyte is 1% by weight or less, the effect of improving ion conductivity may be insignificant, and if the content exceeds 5% by weight, the stability may be reduced.

[0076] The step (6) is a step of winding and recovering the substrate film including the polymer solid electrolyte layer using a rewinder.

[0077] The rewinder can wind up the substrate film including the polymer solid electrolyte into a roll and recover it, and can wind up the substrate film including the polymer solid electrolyte layer by its own drive.

[0078] The recovered substrate film including the polymer solid electrolyte layer may be used as it is, or the polymer solid electrolyte layer may be used in the form of a free-standing film by additionally performing a step of separating the polymer solid electrolyte layer from the substrate film.

[0079] The free-standing film refers to a film that can maintain its film form by itself at room temperature and pressure without a separate support, i.e., without a substrate film.

[0080] The polymer solid electrolyte of the present invention exhibits elasticity, can minimize brittleness, and has the properties of a support that stably contains lithium ions, and therefore is in a suitable form as a polymer solid electrolyte.

[0081] The method for producing the polymer solid electrolyte of the present invention is a roll-to-roll process, which allows continuous production and enables mass production.

[0082] In the present invention, the ionic conductivity of the polymer solid electrolyte is 10 -4 S / cm or more.

[0083] The polymer solid electrolyte has low crystallinity and high ionic conductivity due to its structural characteristics including the cross-linked structure, and thus exhibits ionic conductivity at a level equal to or higher than that of conventional liquid electrolytes, despite being a solid electrolyte, thereby improving the performance of all-solid-state batteries.

[0084] All solid state battery The present invention also relates to an all-solid-state battery including the polymer solid electrolyte, the all-solid-state battery including a negative electrode, a positive electrode, and a polymer solid electrolyte interposed between the negative electrode and the positive electrode, the solid electrolyte being produced by the production method, and having the characteristics described above.

[0085] Specifically, the polymer solid electrolyte is suitable as an electrolyte for an all-solid-state battery because physical cross-links are formed and the crystallinity is reduced by undergoing a freezing and thawing process, thereby improving the ionic conductivity.

[0086] In the present invention, the positive electrode included in the all-solid-state battery includes a positive electrode active material layer, and the positive electrode active material layer may be formed on one surface of a positive electrode current collector.

[0087] The positive electrode active material layer includes a positive electrode active material, a binder, and a conductive material.

[0088] The positive electrode active material is not particularly limited as long as it is a material capable of reversibly absorbing and releasing lithium ions. For example, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), Li[Ni x Co y Mn z M v ]O2 (wherein M is any one or more elements selected from the group consisting of Al, Ga, and In, and 0.3≦x<1.0, 0≦y, z≦0.5, 0≦v≦0.1, and x+y+z+v=1), Li (Li a M b-a-b’ M' b’ )O 2-c A c (wherein 0≦a≦0.2, 0.6≦b≦1, 0≦b'≦0.2, 0≦c≦0.2, M includes one or more selected from the group consisting of Mn and Ni, Co, Fe, Cr, V, Cu, Zn, and Ti, M' is one or more selected from the group consisting of Al, Mg, and B, and A is one or more selected from the group consisting of P, F, S, and N), or a compound substituted with one or more transition metals, such as a compound represented by the formula Li 1+y Mn 2-y O4 (where y is 0-0.33), lithium manganese oxides such as LiMnO3, LiMn2O3, and LiMnO2, lithium copper oxide (Li2CuO2), vanadium oxides such as LiV3O8, V2O5, and Cu2V2O7, and the like, with the chemical formula LiNi 1-y M y Lithium nickel oxide with Ni site, represented by the formula LiMnO2 (where M=Co, Mn, Al, Cu, Fe, Fe, Mg, B or Ga, and y is 0.01-0.3). 2-y M yExamples of such compounds include, but are not limited to, lithium manganese composite oxides represented by Li2Mn3MO8 (where M=Co, Ni, Fe, Cr, Zn or Ta, and y is 0.01-0.1) or Li2Mn3MO8 (where M=Fe, Co, Co, Ni, Cu or Zn), LiMn2O4 in which part of the Li in the chemical formula is replaced with an alkali metal ion, disulfide compounds, and Fe2(MoO4)3.

[0089] The positive electrode active material is contained in an amount of 40 wt% to 80 wt% based on the total weight of the positive electrode active material layer. Specifically, the content of the positive electrode active material is 40 wt% or more or 50 wt% or more and 70 wt% or less or 80 wt% or less. If the content of the positive electrode active material is less than 40 wt%, the connectivity between the wet positive electrode active material layer and the dry positive electrode active material layer may be insufficient, and if it exceeds 80 wt%, the mass transfer resistance may be large.

[0090] The binder is a component that assists in binding the positive electrode active material to the conductive material and the like and binding to the current collector, and is preferably a rubber such as styrene-butadiene rubber, acrylated styrene-butadiene rubber, acrylonitrile copolymer, acrylonitrile-butadiene rubber, nitrile butadiene rubber, acrylonitrile-styrene-butadiene copolymer, acrylic rubber, butyl rubber, fluororubber, polytetrafluoroethylene, polyethylene, polypropylene, ethylene / propylene copolymer, polybutadiene, polyethylene oxide, chlorosulfonated polyethylene, polyvinylpyrrolidone, polyvinylpyridine, polyvinyl alcohol, polyvinyl acetate, polyvinyl chloride, polyphosphazene, polyacrylonitrile, The binder may include one or more selected from the group consisting of styrene-butadiene rubber, polytetrafluoroethylene, carboxymethylcellulose, polystyrene, latex, acrylic resin, phenolic resin, epoxy resin, carboxymethylcellulose, hydroxypropylcellulose, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethylcellulose, cyanoethylsucrose, polyester, polyamide, polyether, polyimide, polycarboxylate, polycarboxylic acid, polyacrylic acid, polyacrylate, lithium polyacrylate, polymethacrylic acid, polymethacrylate, polyacrylamide, polyurethane, polyvinylidene fluoride, and poly(vinylidene fluoride)-hexafluoropropene. Preferably, the binder may include one or more selected from the group consisting of styrene-butadiene rubber, polytetrafluoroethylene, carboxymethylcellulose, polyacrylic acid, lithium polyacrylate, and polyvinylidene fluoride.

[0091] The binder is contained in an amount of 1 to 30% by weight based on the total weight of the positive electrode active material layer, and specifically, the binder content is 1% or more by weight or 3% or more by weight and 15% or less by weight or less by weight or less by weight. If the binder content is less than 1% by weight, the adhesive strength between the positive electrode active material and the positive electrode current collector may decrease, and if it exceeds 30% by weight, the adhesive strength is improved, but the content of the positive electrode active material decreases accordingly, and the battery capacity may decrease.

[0092] The conductive material is not particularly limited as long as it prevents side reactions in the internal environment of the all-solid-state battery, does not cause chemical changes in the battery, and has excellent electrical conductivity. Representative examples include graphite or conductive carbon. Examples of the conductive material include graphite such as natural graphite and artificial graphite, carbon black, acetylene black, ketjen black, denka black, thermal black, channel black, furnace black, and lamp black, carbon-based substances having a graphene or graphite crystal structure, conductive fibers such as carbon fibers and metal fibers, metal powders such as carbon fluoride, aluminum powder, and nickel powder, conductive whiskers such as zinc oxide and potassium titanate, conductive oxides such as titanium oxide, and conductive polymers such as polyphenylene derivatives can be used alone or in a mixture of two or more kinds, but are not necessarily limited to these.

[0093] The conductive material is usually included in an amount of 0.5 wt % to 30 wt % based on the weight of the entire positive electrode active material layer, and specifically, the content of the conductive material is 0.5 wt % or more or 1 wt % or more and 20 wt % or less or 30 wt % or less. If the content of the conductive material is less than 0.5 wt %, the effect of improving electrical conductivity is difficult to be expected, or the electrochemical properties of the battery may be deteriorated, and if the content is more than 30 wt %, the amount of the positive electrode active material is relatively small, and the capacity and energy density may be reduced. The method of incorporating the conductive material into the positive electrode is not greatly limited, and a conventional method known in the art, such as coating on the positive electrode active material, may be used.

[0094] The positive electrode current collector supports the positive electrode active material layer and transfers electrons between an external conductor and the positive electrode active material layer.

[0095] The positive electrode current collector is not particularly limited as long as it does not cause a chemical change in the all-solid-state battery and has high electronic conductivity. For example, the positive electrode current collector can be made of copper, stainless steel, aluminum, nickel, titanium, palladium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, silver, or the like, or an aluminum-cadmium alloy.

[0096] The positive electrode current collector may have a fine uneven structure on the surface thereof or a three-dimensional porous structure in order to strengthen the bonding force with the positive electrode active material layer, and may have various forms such as a film, sheet, foil, mesh, net, porous body, foam, nonwoven fabric, etc.

[0097] The positive electrode may be prepared according to a conventional method, specifically, by mixing a positive electrode active material, a conductive material, and a binder in an organic solvent to prepare a composition for forming a positive electrode active material layer, applying the composition onto a positive electrode current collector, drying the composition, and optionally compressing the composition into a current collector to improve the electrode density. At this time, it is preferable to use an organic solvent that can uniformly disperse the positive electrode active material, the binder, and the conductive material and that can be easily evaporated. Specific examples of the organic solvent include acetonitrile, methanol, ethanol, tetrahydrofuran, water, and isopropyl alcohol.

[0098] In the present invention, the negative electrode included in the all-solid-state battery may include a negative electrode active material layer, and the negative electrode active material layer may be formed on one surface of a negative electrode current collector.

[0099] The negative electrode active material is a lithium ion (Li + The intercalation or deintercalation of lithium ions is not particularly limited, and may be carried out by any suitable method.

[0100] The lithium ion (Li +The material capable of reversibly inserting or de-inserting lithium ions (Li + The material capable of reacting with lithium (Li) to reversibly form a lithium-containing compound is, for example, tin oxide, titanate, or silicon. The lithium alloy is, for example, an alloy of lithium (Li) and a metal selected from the group consisting of sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), radium (Ra), aluminum (Al), and tin (Sn).

[0101] Preferably, the negative electrode active material is lithium metal, specifically in the form of a lithium metal thin film or lithium metal powder.

[0102] The negative active material may be contained in an amount of 40 wt% to 80 wt% based on the total weight of the negative active material layer. Specifically, the content of the negative active material is 40 wt% or more or 50 wt% or more and 70 wt% or less or 80 wt% or less. If the content of the negative active material is less than 40 wt%, the connectivity between the wet negative active material layer and the dry negative active material layer may be insufficient, and if it exceeds 80 wt%, the mass transfer resistance may be large.

[0103] The binder is the same as that described above in the positive electrode active material layer.

[0104] The conductive material is the same as that described above in the positive electrode active material layer.

[0105] The negative electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and examples of the negative electrode current collector that can be used include copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, aluminum-cadmium alloy, etc. Similarly to the positive electrode current collector, the negative electrode current collector can be in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc., with fine irregularities formed on the surface.

[0106] The method for manufacturing the anode is not particularly limited, and the anode may be manufactured by forming an anode active material layer on the anode current collector using a method for forming a layer or film commonly used in the art. For example, methods such as compression bonding, coating, deposition, etc. may be used. In addition, the anode of the present invention also includes a case where a thin metallic lithium film is formed on the metal plate by initial charging after assembling a battery without a thin lithium film on the anode current collector.

[0107] The present invention also provides a battery module including the all-solid-state battery as a unit cell, a battery pack including the battery module, and a device including the battery pack as a power source.

[0108] In this case, specific examples of the device include, but are not limited to, power tools powered by an electric motor, electric vehicles including electric vehicles (EV), hybrid electric vehicles (HEV), plug-in hybrid electric vehicles (PHEV), etc., electric bicycles (E-bikes), electric two-wheeled vehicles including electric scooters (E-scooters), electric golf carts, and power storage systems.

[0109] Below, preferred examples are shown to aid in understanding the present invention. However, the following examples are merely illustrative of the present invention, and it will be apparent to those skilled in the art that various changes and modifications are possible within the category and technical spirit of the present invention, and it is natural that these changes and modifications fall within the scope of the appended claims.

[0110] In the following examples and comparative examples, polymer solid electrolytes were prepared using polymers containing cross-linkable functional groups, the molar ratio of the cross-linkable functional groups to lithium ions, and with or without the application of a freezing / thawing process, as shown in Table 1 below.

[0111] [Table 1]

[0112] Example 1 PVA (Mw: 89,000 g / mol, degree of hydrolysis: >99%) was mixed with water to prepare a 10 wt% PVA aqueous solution. LiTFSI was added to the PVA aqueous solution and stirred to produce a solution containing PVA, a polymer having cross-linking functional groups, and LiTFSI, a lithium salt. At this time, the molar ratio ([Li] / [OH]) of "OH" contained in the cross-linking functional groups of the PVA to "Li" contained in the lithium salt was set to 0.4.

[0113] The solution was poured into a mixer and then coated by a solution casting method onto a substrate film, SS foil, which was fed to a conveying path by an unwinder, and then conveyed to a freezing section and frozen at -20°C for 24 hours, and then conveyed to a thawing section and thawed at 25°C to produce a polymer solid electrolyte layer on the substrate film. The substrate film including the produced polymer solid electrolyte layer was wound and collected using a rewinder. The substrate film was then peeled off to obtain a free-standing film-like polymer solid electrolyte.

[0114] Example 2 A polymer solid electrolyte was produced in the same manner as in Example 1, except that PVA having a weight average molecular weight (Mw) of 85,000 g / mol was used.

[0115] Example 3 A polymer solid electrolyte was produced in the same manner as in Example 1, except that PVA having a weight average molecular weight (Mw) of 100,000 g / mol was used.

[0116] Example 4 A polymer solid electrolyte was produced in the same manner as in Example 1, except that the molar ratio ([Li] / [OH]) of the cross-linking functional group “OH” of the PVA to the “Li” of the lithium salt was 0.1.

[0117] Example 5 A polymer solid electrolyte was produced in the same manner as in Example 1, except that the molar ratio ([Li] / [OH]) of the cross-linking functional group “OH” of the PVA to the “Li” of the lithium salt was 0.2.

[0118] Example 6 A polymer solid electrolyte was produced in the same manner as in Example 1, except that the molar ratio ([Li] / [OH]) of the cross-linking functional group “OH” of the PVA to the “Li” of the lithium salt was set to 0.3.

[0119] Comparative Example 1 A polymer solid electrolyte was produced in the same manner as in Example 1, except that a solution containing PVA, which is a polymer having a cross-linkable functional group, and LiTFSI, which is a lithium salt, was applied onto an SS foil (SS foil) as a substrate, and then dried at 80°C.

[0120] Comparative Example 2 A polymer solid electrolyte was produced in the same manner as in Example 1, except that PEO, which is a polymer having no cross-linking functional groups, was used instead of PVA.

[0121] Comparative Example 3 A polymer solid electrolyte was produced in the same manner as in Comparative Example 1, except that a solution containing PVA, a polymer having a cross-linking functional group, and LiTFSI, a lithium salt, was applied onto an SS foil substrate, and then dried at room temperature (25°C).

[0122] Comparative Example 4 A polymer solid electrolyte was produced in the same manner as in Example 1, except that a 35% aqueous solution of poly(acrylic acid, PAA) (Mw: 100,000 g / mol) was used instead of PVA.

[0123] Comparative Example 5 A polymer solid electrolyte was produced in the same manner as in Example 1, except that PVA having a weight average molecular weight (Mw) of 50,000 g / mol was used.

[0124] Comparative Example 6 A polymer solid electrolyte was produced in the same manner as in Example 1, except that PVA having a weight average molecular weight (Mw) of 146,000 g / mol was used.

[0125] Comparative Example 7 A polymer solid electrolyte was produced in the same manner as in Example 1, except that the molar ratio ([Li] / [OH]) of “OH” contained in the cross-linking functional group of the PVA to “Li” of the lithium salt was 0.5.

[0126] Comparative Example 8 A polymer solid electrolyte was produced in the same manner as in Example 1, except that the molar ratio of “OH” contained in the cross-linking functional group of PVA to “Li” of the lithium salt ([Li] / [OH]) was set to 0.52.

[0127] Experimental Example 1 In order to measure the ionic conductivity of the film-shaped polymer solid electrolyte prepared in the examples and comparative examples, 2 The solid polymer electrolyte was punched into a circular shape of a desired size, and the punched solid polymer electrolyte was placed between two pieces of stainless steel (SS) to prepare a coin cell.

[0128] The resistance was measured using an electrochemical impedance spectrometer (EIS, VM3, Bio Logic Science Instrument) at 25° C., with an amplitude of 10 mV and a scan range of 500 KHz to 20 MHz, and the ionic conductivity of the polymer solid electrolyte was calculated using the following Equation 1.

[0129]

number

[0130] In the above formula 1, σ i is the ionic conductivity of the polymer solid electrolyte (S / cm), R is the resistance of the polymer solid electrolyte (Ω) measured by the electrochemical impedance spectrometer, L is the thickness of the polymer solid electrolyte (μm), and A is the area of ​​the polymer solid electrolyte (cm 2 )

[0131] The ionic conductivity of the polymer solid electrolyte calculated using Equation 1, whether a freestanding film was formed, and the results of observing the appearance of the polymer solid electrolyte are shown in Table 2. Here, whether the freestanding film was formed (formed: ◯, not formed: X) and the appearance of the polymer solid electrolyte were observed with the naked eye.

[0132] [Table 2]

[0133] As shown in Table 2, it was confirmed that a polymer solid electrolyte in the form of a freestanding film can be prepared by using PVA having an appropriate range of molecular weight and a molar ratio ([Li] / [OH]) of the crosslinkable functional group and the lithium of the lithium salt as the polymer containing the crosslinkable functional group and applying a freezing and thawing process (Examples 1, 2, 3, 5, and 6).

[0134] In Comparative Example 4, PAA was used as the polymer containing a cross-linkable functional group. Since PAA froze during the freezing step after the formation of the coating film and became liquid again during the thawing step, a free-standing film-like polymer solid electrolyte could not be produced.

[0135] In Comparative Example 5, the molecular weight of the PVA was low, so that the electrolyte was produced in a liquid state, and a free-standing film-like polymer solid electrolyte was not obtained.

[0136] In addition, in Comparative Example 6, since the molecular weight of PVA was high, a solution for forming a coating film could not be obtained, and the electrolyte production process could not be carried out.

[0137] In addition, in Example 4, a brittle film was produced because the molar ratio of cross-linkable functional groups to lithium ([Li] / [OH]) was small, and it was confirmed that the brittle film had significantly lower ionic conductivity than a free-standing film.

[0138] In addition, in Comparative Example 7, the molar ratio of cross-linkable functional groups to lithium ([Li] / [OH]) was large, so a highly viscous gel was produced instead of a film. The gel had high ionic conductivity, but it was in the form of a gel rather than a film, and it was confirmed that it was unsuitable for use as a polymer solid electrolyte. A gel state refers to a solid state with such low mechanical strength that it cannot be peeled off from the substrate, or a liquid state with high viscosity, making it difficult to use as a polymer solid electrolyte.

[0139] In addition, in Comparative Example 8, the molar ratio of cross-linkable functional groups to lithium ([Li] / [OH]) was larger than in Example 1, and a highly viscous gel was produced instead of a film. Although the gel had high ionic conductivity, it was confirmed that it was unsuitable for use as a polymer solid electrolyte because it was in the form of a gel rather than a film.

[0140] In Comparative Example 1, an electrolyte was prepared using a high-temperature drying process at 80°C, resulting in a gel-like electrolyte with high viscosity. A uniform coating film could not be formed on the substrate, and air bubbles, aggregation, and warping occurred during coating film formation.

[0141] Comparative Example 2 was an electrolyte prepared using PEO that did not have cross-linking functional groups, and was in a liquid state rather than a film state.

[0142] In Comparative Example 3, the polymer solid electrolyte was prepared using a room temperature drying process. It was found that the polymer solid electrolyte had low mechanical strength and low ionic conductivity due to the absence of physical cross-links formed by the freezing and thawing processes.

[0143] FIG. 2 is a graph showing the tendency of the ionic conductivity of the electrolyte depending on the molar ratio ([Li] / [OH]) of the cross-linkable functional group to the lithium salt.

[0144] Referring to FIG. 2, the molar ratio of lithium to cross-linking functional groups ([Li] / [OH], n Li / n PVA It can be seen that the ionic conductivity of the polymer solid electrolyte increases as the temperature increases. Comparative Example 3 was produced by a room temperature drying process and had a significantly low ionic conductivity.

[0145] FIG. 3 is a photograph showing the electrolyte morphology depending on the molar ratio of cross-linking functional group to lithium ([Li] / [OH]).

[0146] Referring to FIG. 3, Example 4, in which the molar ratio of cross-linking functional group to lithium ([Li] / [OH]) was 0.1, produced a brittle film, Comparative Example 7, in which the molar ratio was 0.5, produced a highly viscous gel, and Examples 1, 5, and 6, in which the molar ratio was greater than 0.1 and less than 0.5, produced polymer solid electrolytes in the form of films.

[0147] Example 7 A polymer solid electrolyte was produced in the same manner as in Example 1, except that two cycles of freezing and thawing were performed.

[0148] Example 8 A polymer solid electrolyte was produced in the same manner as in Example 1, except that the freezing and thawing steps were performed three times.

[0149] Example 9 A polymer solid electrolyte was produced in the same manner as in Example 1, except that the freezing and thawing steps were repeated five times.

[0150] Example 10 A polymer solid electrolyte was produced in the same manner as in Example 1, except that the freezing and thawing steps were repeated 10 times.

[0151] Comparative Example 9 PVA (Mw: 89,000 g / mol; hydrolysis degree: >99%) was mixed with water to prepare a 10 wt% PVA aqueous solution, which was then coated on SS foil and dried at high temperature (90°C, 3 hours) to prepare a PVA film.

[0152] Comparative Example 10 A PVA film was produced in the same manner as in Comparative Example 9, except that boric acid was added as a crosslinking agent.

[0153] Experimental Example 2 An experiment was carried out to compare the presence or absence and the degree of formation of a cross-linked structure inside the polymer solid electrolyte.

[0154] Since the purpose of the present study was to compare only the presence or absence and the degree of formation of a crosslinked structure, the PVA film of Comparative Example 9, which did not contain a crosslinked structure, and the PVA film of Comparative Example 10, in which a chemical crosslinked structure was formed by a crosslinking agent, were used for comparison.

[0155] (1) Check the degree of swelling The test samples were immersed in water at room temperature (25°C) for 12 hours, and the degree of swelling of the samples was then confirmed and evaluated according to the following criteria.

[0156] <Criteria for determining swelling degree> ◎: Swelling of 80% or more of the total volume.

[0157] ○: Swelling of 50% or more of the total volume.

[0158] △: Swelling of 20% or more of the total volume.

[0159] X: Swelling of less than 10% of the total volume.

[0160] (2) Modulus The modulus was measured on a Universal testing machine (UTM).

[0161] [Table 3]

[0162] Referring to Table 3, Example 1 and Examples 7 to 10 show a modulus of a certain level or more as a polymer solid electrolyte prepared by a freezing and thawing process, and the swelling degree also decreases as the number of cycles of the freezing and thawing process increases. In general, the swelling degree and mechanical properties of a polymer are greatly affected by the degree of crosslinking. The formation of crosslinking points increases the internal resistance of the polymer chain, causing an increase in swelling resistance and mechanical strength. In particular, the formation of physical crosslinks based on the freezing and thawing process is affected by the number of repetitions of the freezing and thawing process. As the number of cycles increases, the modulus increases and the swelling degree decreases, so it can be seen that the crosslink structure increases as the number of cycles increases. Example 1 shows that the swelling degree is 50% or more of the total volume, which is a result measured after 12 hours at room temperature, and is suitable as a property required for a polymer solid electrolyte for an all-solid-state battery.

[0163] It was found that the PVA film of Comparative Example 9 was swollen to 80% or more of its total volume, which indicates that no cross-linked bond structure was present inside the polymer.

[0164] The PVA film of Comparative Example 10 had a chemical cross-linked structure formed by the addition of boric acid as a cross-linking agent, and it was found that the modulus was lower than that of Comparative Example 9, in which no cross-linked structure was formed.

[0165] The PVA film of Comparative Example 10 had a reduced modulus compared to that of Comparative Example 9 due to the formation of a chemical cross-linked structure, reduced crystallinity, and increased polymer flexibility.

[0166] Meanwhile, unlike the manufacturing methods of Comparative Examples 9 and 10, Examples 1 and 7 to 10 correspond to PVA films in the form of hydrogels based on physical cross-linking formed using a freezing and thawing process. This shows a tendency that the modulus increases as the cross-linking increases. In Examples 1 and 7 to 10, the cross-linked structure increases as the number of cycles of the freezing and thawing process increases, and the modulus also increases. Through the freezing and thawing process, some of the cross-linking functional groups contained in the PVA form localized microcrystals, and the localized microcrystals act as cross-linkable junction points, increasing the modulus.

[0167] Although the present invention has been described above with reference to limited examples and drawings, the present invention is not limited thereto, and it is obvious that various modifications and variations can be made by a person having ordinary knowledge in the technical field to which the present invention pertains within the technical spirit of the present invention and the equivalent scope of the claims described below.

Claims

1. (1) preparing a polymer solution containing a cross-linkable functional group and a solution for forming a polymer solid electrolyte containing a lithium salt; (2) unwinding the base film using an unwinder and supplying it to a conveying path; (3) applying the polymer solid electrolyte forming solution onto the substrate film to form a coating film; (4) conveying the substrate film having the coating film formed thereon to a freezing section and freezing the coating film; (5) transferring the substrate film having the frozen coating film formed thereon to a thawing section and thawing the frozen coating film to manufacture a polymer solid electrolyte layer; and (6) A method for producing a polymer solid electrolyte, comprising the step of winding and recovering the substrate film including the polymer solid electrolyte layer using a rewinder.

2. 2. The method of claim 1, wherein the crosslinkable functional group comprises at least one selected from the group consisting of a hydroxyl group, a carboxyl group, and an amide group.

3. 2. The method of claim 1, wherein the weight average molecular weight (Mw) of the polymer having the cross-linking functional group is 80,000 g / mol to 130,000 g / mol.

4. The polymers containing the crosslinkable functional groups include polyvinyl alcohol (PVA), gelatin, methylcellulose, agar, dextran, poly(vinyl pyrrolidone), polyethylene oxide, polyacrylamide, starch-carboxymethylcellulose, hyaluronic acid-methylcellulose, and the like.

2. The method for producing a polymer solid electrolyte according to claim 1, comprising at least one selected from the group consisting of N-isopropylacrylamide, N-isopropylacrylamide, chitosan, poly(N-isopropylacrylamide), and amino-terminated polyethylene glycol.

5. The lithium salt is LiNO 3 , LiOH, LiCl, LiBr, LiI, LiClO 4 , LiBF 4 , LiB 10 C 10 , LiPF 6 , LiCF 3 SO 3 , LiCF 3 CO 2 , LiAsF 6 , LiSbF 6 , LiAlCl 4 , C.H. 3 SO 3 Li, C.F. 3 SO 3 Li, LiSCN, LiC(CF 3 SO 2 ) 3 , (CF 3 SO 2 ) 2 NLi, and (FSO 2 ) 2 The method for producing a polymer solid electrolyte according to claim 1 , comprising the step of:

6. 2. The method of claim 1, wherein the polymer solution containing the cross-linkable functional group contains the polymer containing the cross-linkable functional group in an amount of 5 to 20% by weight based on the total weight of the polymer solution containing the cross-linkable functional group.

7. The method for producing a polymer solid electrolyte according to claim 1 , wherein the solvent of the polymer solution containing the cross-linking functional group is water.

8. 2. The method for producing a polymer solid electrolyte according to claim 1, wherein a molar ratio ([Li] / [G]) of lithium ([Li]) of the lithium salt to a cross-linking functional group ([G]) of the polymer is greater than 0.1 and less than 0.

5.

9. 2. The method for producing a polymer solid electrolyte according to claim 1, wherein the freezing is performed at −30° C. to −10° C.

10. The method for producing a polymer solid electrolyte according to claim 1 , wherein the thawing is performed at 15° C. to 35° C.

11. The method for producing a polymer solid electrolyte according to claim 1 , wherein the freezing in step (4) and the thawing in step (5) are repeated.

12. The polymer solid electrolyte includes an amorphous polymer chain having a cross-linked structure and the cross-linkable functional group, the cross-linked structure includes (a) a cross-link between the cross-linkable functional groups, (b) a cross-link between the cross-linkable functional groups and a solvent, and (c) a bond between the cross-linkable functional groups and a lithium salt; the (a) cross-linking bond between the cross-linkable functional groups includes a hydrogen bond, the (b) crosslinking between the crosslinkable functional group and the solvent includes a hydrogen bond; 2. The method for producing a polymer solid electrolyte according to claim 1, wherein the (c) bond between the cross-linkable functional group and the lithium salt includes a bond based on Lewis acid-base interaction.

13. The method for producing a polymer solid electrolyte according to claim 12 , wherein the solvent contains water.

14. The method for producing a polymer solid electrolyte according to claim 12, wherein the cross-linked structure and the amorphous polymer chains including the cross-linkable functional groups are formed in the step (4).

15. 2. The method for producing a polymer solid electrolyte according to claim 1, further comprising the step of immersing the polymer solid electrolyte layer in a liquid electrolyte and then drying the liquid electrolyte after the step (5) and before the step (6).

16. The ionic conductivity of the polymer solid electrolyte is 10 -4 2. The method for producing a polymer solid electrolyte according to claim 1, wherein the viscosity is 1.0 S / cm or more.

17. An all-solid-state battery comprising a polymer solid electrolyte produced by the method according to claim 1.

Citation Information

Patent Citations

  • All-solid battery, hybrid structure solid electrolyte film and manufacturing methods thereof

    JP2019029330A

  • Solid electrolyte membrane with film and method for producing same

    WO2015133388A1

  • Solid-state polymer electrolyte membrane with grid structure, and preparation method thereof

    CN112259788A